Effect of foliar application of selected micronutrients and growth regulators on tuber development , yield and fortification status of sweet potato (Ipomoea batatas L.). - Arya S.R (Department of Plant Physiology , College of Agriculture, 2019)
A field experiment entitled “ Effect of foliar application of selected micro nutrients and growth regulators on tuber development, yield and fortification status of sweet potato (Ipomoea batatas L.)” was conducted at the Instructional farm, College of Agriculture, Vellayani during the period 2017-2019 with an objective to enhance the qualitative and quantitative attributes in sweet potato (Ipomoea batatas L.). Foliar application of selected micronutrients and growth regulators were carried out to study their effect on growth, development and changes in fortification status of sweet potato tubers and leaves. The sweet potato variety used for the experiment was Bhu Krishna. The technical programme consisted of 17 treatments and 3 replications with the design simple RBD. The treatments were C1 : NPK (as per POP) , C2 : NPK (as per POP) with water spray, T1 : C1+ FN (MN mixture( * ) 0.01% each , T2 : C1+ FN (MN mixture( * ) 0.05% each , T3 : C1+ FN (MN mixture( * ) 0.1% each , T4 : T1+ Ethrel 250 ppm , T5 : T1+ Ethrel 500 ppm , T6 : T1+ CCC 250 ppm , T7 : T1+ CCC 500 ppm , T8 : T2+ Ethrel 250 ppm , T9 : T2+ Ethrel 500 ppm , T10: T2+ CCC 250 ppm , T11: T2+ CCC 500 ppm, T12: T3+ Ethrel 250 ppm , T13: T3+ Ethrel 500 ppm , T14: T3+ CCC 250 ppm and T15: T3+ CCC 500 ppm [*MN mixture (Zn+Fe+B+Mn)]. Except C1, for all other treatments foliar sprays were given 3 times ie. at 30 days interval(30 DI). All the biometric and physiological parameters were taken at 25th,50th,75th and 100th days after planting and the quality parameters were taken at harvest. The results revealed that the micronutrients and growth regulators had significant influence on most of the biometric parameters, physiological parameters as well as quality parameters. Tuber characters such as tuber length, tuber diameter, tuber weight and tuber yield were found to be best in plants under the treatment T15 (T3+ CCC 500 ppm at 30DI) and it was on par with T13(T3+Ethrel 500ppm). Branch length (155.50cm), shoot weight (612 g) and specific leaf area (389.44 cm2 g-1) were found to be best in plants under the treatment T3(C1+ FN (MN mixture( * ) 0.1% each at 30DI). Number of leaves also were found to be higher in T3 (91.33) and it was on par with T2, T13 and T15. Cycocel and ethrel are growth retardants and they were found to have dwarfing effect on plants and hence shoot length and shoot weight did not increase in the treatments, T15(T3+ CCC 500at 30DI) and T13(T3+ Ethrel 500 ppm at 30DI) and on the other hand the number of leaves got positively influenced in both these treatments T15 and T13. Except transpiration rate all physiological parameters viz., total chlorophyll content (2.25 mg g-1), caroteinoid content (0.87mg g-1), stomatal conductance (131.33 mmole H2O m-2 s-1), photosynthetic rate (4.49 µmole CO2 m-2 s-1) and water use efficiency (5.35 mmol CO2 mol-1 H2O) were found to be best in plants under the treatment T15 (T3+ CCC 500 ppm) and T13 was on par with T15 in all these physiological parameters studied. Mineral constituents; N (0.614 %), P (0.056%), K (0.489%),Fe (16.30 mg kg-1), Zn (15.07 mg kg-1), Mn (7.37 mg kg-1) and B (1.27 mg kg-1) as well as other quality parameters like total phenol (13.33mg g-1), total sugar (34.48 mg g-1) and protein content (38.40mg g-1) were found to be higher in tubers under the treatment T15 (T3+ CCC 500 ppm) followed by treatment T13 which is considered as the second best treatment with respect to mineral content in tubers. Overall, the combined treatments of micronutrients along with growth regulators were found most effective in influencing quality parameters. Treatment T15 (ie.,NPK as per POP along with foliar nutrition of micronutreint mixture (Fe+Zn+Mn+B @ 0.1% each ) + cycocel (500ppm) at 30 days interval ) was found to be the best in terms of improving both the quantitative and qualitative attributes in sweet potato. Hence it is concluded that the treatment T15 improved the growth and development of plants, physiological parameters of leaves, tuber yield as well as fortification status of sweet potato tubers. Thus this study helped in identifying the best treatment combination of micronutrients and growth regulators for improving growth, development, yield and fortification status in sweet potato.